FunResDB-A web resource for genotypic susceptibility testing of Aspergillus fumigatus - Weber, Michael; Spiess, Birgit; Buchheidt, Dieter (Medical mycology, 2018)
Therapy of invasive aspergillosis is becoming more difficult due to the emergence of azole resistance in Aspergillus fumigatus. A majority of resistant strains carries mutations in the CYP51A gene. Due to a lack of sensitivity of culture-based methods, molecular detection of A. fumigatus has become an important diagnostic tool. We set up the database FunResDB (www.nrz-myk.de/funresdb) to gather all available information about CYP51A-dependent azole resistance from published literature. In summary, the screening resulted in 79 CYP51A variants, which are linked to 59 nonsynonymous mutations. A tailor-made online sequence analysis tool allows for genotypic susceptibility testing of A. fumigatus.
Advance Access Publication Date: 11 March 2017
Gesehen am 28.06.2019